133 Empowering junior leaders during COVID-19: reflections from a team at North Middlesex university hospital. (16th November 2020) - Zosmer, Maya; Pleming, Joanna; Papalouca, Kyriacos Loizos; Maturana, Mailis Michaud; Hickingbotham, Hannah Jane; Ozbek, Leyla; Mills, Charlotte Emily; Gil, Eliza; Weller, Sophie Joanne; Doxey, Richard Philip; Radia, Pooja
Abstract : Introduction: North Middlesex University Hospital (NMUH) was one of the first hospitals affected by COVID-19, and one of the most pressured trusts dealing with the crisis in the UK. We describe a junior led initiative to manage the rapidly evolving situation and how lessons learnt from this experience can inform preparation for future events. Methods: In response to escalating issues on the ground, junior doctor representatives formed the Junior COVID-19 Working Group (JCWG) and worked alongside senior leadership to address front line challenges during the peak, as well as designing and implementing a trust-wide workforce restructuring project and an emergency rota. Results: With support from senior leadership, the JCWG was able to influence higher decision making and achieve numerous important interventions. Junior led rota design and workforce restructuring resulted in favourable outcomes for doctors' morale and perceptions of patient safety. Discussion: In the context of a novel crisis, junior leadership and engagement with higher management is essential in understanding and managing rapidly evolving situations on the front line. Our model highlights that in planning for future similar events, trusts should seek to champion junior led change via similar models, as well as invest in nurturing and training junior leaders.